2018
DOI: 10.3389/fendo.2018.00569
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 in Secretory Organ Cancer

Abstract: Mammalian silent information regulator 1 (SIRT1) is reported to play a role in cancers of the secretory organs, including thyroid, pancreatic endocrine, and ovarian tumors [1, 2, 3, 4]. A recent meta-analysis conducted on 37 selected studies of human cancers analyzed the correlations of overall survival (OS), disease-free survival (DFS) and relapse-free survival (RFS) with SIRT1 expression [5]. This study reported that SIRT1 overexpression was associated with a worse OS in liver and lung cancers, while it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…SIRT1 is ubiquitously expressed in the nucleus but shuttles between the nucleus and cytoplasm 4 . Similar to other HDACs, aberrant SIRT1 expression is reported in multiple human malignancies, namely, gastric, colon, prostate, and ovarian cancers, as well as breast cancer 5 - 11 . The implications of SIRT1 in breast cancer occurrence and progression have been investigated over recent years.…”
Section: Introductionmentioning
confidence: 79%
“…SIRT1 is ubiquitously expressed in the nucleus but shuttles between the nucleus and cytoplasm 4 . Similar to other HDACs, aberrant SIRT1 expression is reported in multiple human malignancies, namely, gastric, colon, prostate, and ovarian cancers, as well as breast cancer 5 - 11 . The implications of SIRT1 in breast cancer occurrence and progression have been investigated over recent years.…”
Section: Introductionmentioning
confidence: 79%
“…As previously mentioned, NAM increases the levels of NAD + , boosts energy metabolism and protects cells from oxidative stress [39]. NAM also inhibits SIRT1 and PARP1, both of which have been shown to be up-regulated in multiple cancers [39,48,[137][138][139]. However, while it suppresses Despite the aforementioned evidence, more studies are needed to unravel NAM's entire molecular mechanism in diverse cancer scenarios, before its widespread implementation into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, another study also reported that overexpression of SIRT1 in HCC cells is positively associated with micro vascular invasion and metastasis through the stimulation of PGC-1α-mediated mitochondrial biogenesis resulting in poor treatment outcome [55]. This was also supported by Frazzi, who showed that an overexpression of SIRT1 results in poor treatment outcome and short life expectancy in patients with HCC [56]. But be sure that the subcellular localization of SIRT1 can be varied from cell to cell, and some cells appeared to have nuclear expression of SIRT1 whereas others expressed it within the cytoplasm or in both [57].…”
Section: Role Of Sirt1 In Hepatocellular Carcinoma Progressionmentioning
confidence: 53%